The Language Acquisition in International Baccalaureate : A Systematic Literature Review of Potentials and Challenges - Faris Sholakhuddin; Joko Nurkamto; Sumardi (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2026)
The trend in deep learning in English language education has encouraged greater attention toward curriculum models that connect language learning with meaningful classroom interaction. Within this research, the International Baccalaureate (IB) Language Acquisition framework has gained attention for its learner-centred and inquiry-oriented approach to language education. This study aims to examine the potentials and challenges of IB Language Acquisition in improving English language learning. Using a systematic literature review design guided by PRISMA, the study selected ten peer-reviewed articles published between 2015 and 2025 from Scopus, ERIC, SAGE Journals, Google Scholar, and Semantic Scholar. Our findings show that IB Language Acquisition engage deeper learning by emphasising language as part of meaning-making, identity construction, inquiry, conceptual engagement, critical thinking, and multilingual interaction. The findings also indicate a shift from form-focused language learning toward sociocultural and epistemic perspectives where language functions as a medium for constructing understanding and participating in learning processes. However, the implementation of IB Language Acquisition remains shaped by contextual challenges, including procedural inquiry practices, unequal institutional readiness, assessment demands, and tensions surrounding multilingualism and academic English expectations.